The role of implicit contract terms as a determinant of contractual consequences - Bailly, Chantal (Stellenbosch University, 2005)
Banks are one of the most important elements in the economic cycle of modem society. As money replaced bartering banks have gradually moved into the pivotal point of the relations between participants in the economic cycle. No project can be realized without money today. On the one hand, there are the investors who, irrespective of the amount, entrust their assets to the banks. On the other hand, there are those whose financial needs require the granting of some form of credit. Banks operating in these contexts clearly bear important responsibilities towards the different parties. A third party, the state, is also interested in a well-functioning banking establishment. Economic stability, without which there can be no political stability, cannot otherwise be ensured. The state is accordingly keenly interested in maintaining the operability of this system. To this end, various laws are made in the respective countries aimed at supervising the banking industry. This work deals with some of the legislation relating to bank supervision in the Federal Republic of Germany and the Republic of South Africa. In the various chapters certain aspects of bank supervision in the two countries are identified, juxtaposed and compared. The reasons for any differences are sought, discussed and where possible explained. From a historical point of view, the two countries developed differently. Nevertheless, the need to regulate this sector through legislative means arose at an early stage in both. Unfortunately, the catalyst for legislative development was mostly some or other financial crisis. Any measures for supervising banks must, to be binding, be constitutional. In this regard much must still be done in South Africa due to the fact that the New Constitution has only been in force since 1996. Thus certain regulations stemming from the Banks Act 90 of 1994 need to be reconsidered in the light of the constitution. Bank supervisory activity is performed by a national institution in both countries. Germany avails itself of an independent authority. However, in South Africa it is one of the tasks of the central bank which has established a specific office for this purpose. Legal and natural persons alike are subject to such supervision. Diverse other government institutions provide support for such supervisory work in both countries. The scope of banking supervision, that is the persons and transactions affected, is broad and also finely meshed. Both systems list a number of banking transactions that are subject to their supervision. This affects all domestic banks and all foreign banks that are domestically active. Access to the banking business is only permitted in both countries after an appropriate license has been granted. The license can be conditional. Moreover, both systems make provision for the revocation of the license in appropriate circumstances. The conducting of banking business without the necessary permission is forbidden in both countries under the threat of legal punishment. It is well recognized in modem society that legal subjects should be protected against the decisions of those who wield state power. The possible remedies of those affected by the decisions of the public authorities responsible for banking supervision in the different countries are investigated in conclusion.
Keywords: Contracts; Good faith

The legal regulation of corporate governance with reference to international trends - Horn, Roelof Combrinck (University of Stellenbosch, 2005)
Corporate governance is defined as the system by which companies are managed and controlled. The concept came to the fore with the Cadbury Report in England in 1992 and has since been the topic of much academic discussion. The recent collapse of companies like Enron and WorldCom raised serious questions about international corporate governance practices. This has resulted in widespread reform. In the United States large-scale prescriptive measures were implemented through the enactment of the Sarbanes-Oxley Act. The United Kingdom persisted with their principle-based approach of comply or explain, although some amendments were made to the Combined Code through a joint effort by the Co-ordinating Group on Audit and Accounting Issues, the Smith Report and the Higgs Report. In Australia change took the form of the ASX Corporate Governance Principles and CLERP 9. South Africa, influenced by its common law background, followed a similar approach to that of the United Kingdom but has recently adopted a more prescriptive approach similar to that of the US. The King Committee was set up to review corporate governance in South Africa and two reports report were published – one in 1994 and another in 2002. Amendments to the JSE Listings Requirements followed. The Konar Report made recommendations on the reform of the accounting and auditing profession. The Department of Trade and Industry has recently launched a review of South African company law in conjunction with a review of the audit and accounting professions. These recent developments in company law will however not be discussed in depth as it is at a very early stage and is still subject to change. The aim of this study is to evaluate and determine whether or not the reform in South Africa is adequate to address the questions raised by recent corporate scandals in South Africa. The question also has to be asked whether South Africa should follow international trends in reform just for the sake of reforming. This requires an understanding of the principles underlying corporate governance and the reasons for the existence of corporate governance rules. With the increasing separation between ownership and control the accountability of directors has waned considerably. When addressing corporate governance issues, this must be kept in mind constantly. While the focus of recent reform has been on the company, its directors and auditors, the role of shareholders should not be ignored. What is needed to prevent directors and managers from abusing their positions of power are more informed and involved shareholders. The different role players must also cooperate in developing a culture of ethical behaviour and an environment of openness and accountability.

L'impact juridique des nouvelles dispositions de la Loi sur les normes du travail en matière de harcèlement psychologique sur le régime légal préexistant - Bourgault, Julie (Université Laval, 2005)
Ce mémoire cherche à déterminer l’impact juridique de l’adoption des nouvelles dispositions en matière de harcèlement psychologique au travail dans la Loi sur les normes du travail, sur le régime légal préexistant concernant le harcèlement au travail. En effet, la généralité des termes de la définition utilisée englobe un grand nombre de situations déjà couvertes par d’autres recours. L’étude des dispositions législatives des différents régimes, ainsi que de la jurisprudence sur le harcèlement en milieu de travail permet de constater que les recours préexistants conservent une utilité pour les victimes. Toutefois, le choix du recours doit tenir compte des différents modèles de compétence, qui varient selon les dispositions et la nature du litige, dans son contexte factuel.
Keywords: Harcèlement (travail); Harcèlement psychologique; Normes du travail